The behavior of the directional suffixes in the Ashaninka language: cognitive analysis - Infante Seminario, Luz Mery (2015)
This article is based mainly on a bibliographic study. In general, it focuses on the analysis of directional Ashaninka suffixes from the Cognitive Linguistics approach. Studies on this Arawak family language deal with suffixes descriptively, arguing that they provide different meanings, figurative or non-figurative, depending on the verb to which they are added. That is, the suffixes have other meanings outside the scope of directionality. The analysis based on image schemata, one of the basic principles of Cognitive Linguistics; offer an explanation of the motivation of those who speak Ashaninka in their use of such suffixes with figurative or metaphorical sense.